2019
DOI: 10.1093/aob/mcz137
|View full text |Cite
|
Sign up to set email alerts
|

Elevated micro-topography boosts growth rates in Salicornia procumbens by amplifying a tidally driven oxygen pump: implications for natural recruitment and restoration

Abstract: Background and Aims The growth rate of pioneer species is known to be a critical component determining recruitment success of marsh seedlings on tidal flats. By accelerating growth, recruits can reach a larger size at an earlier date, which reduces the length of the disturbance-free window required for successful establishment. Therefore, the pursuit of natural mechanisms that accelerate growth rates at a local scale may lead to a better understanding of the circumstances under which new esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(74 citation statements)
references
References 61 publications
2
67
0
2
Order By: Relevance
“…Microtopography is small-scale vertical relief that provides a diversity of safe sites for seeds and seedlings (Urbanska, 1997;Peach and Zedler, 2006). Diverse microtopography can protect seedlings by providing areas with varying environmental conditions (i.e., differing temperatures, soil characteristics, redox levels, and water retention abilities) and has been shown to improve plant establishment, survival, and species richness in restorations (Urbanska, 1997;Peach and Zedler, 2006;Fivash et al, 2020;Mossman et al, 2020;Ott et al, 2020). Furthermore, the heterogeneity at a site can result in more complex plant communities and facilitate the development of ecosystem functions (Larkin et al, 2016).…”
Section: Microtopographymentioning
confidence: 99%
“…Microtopography is small-scale vertical relief that provides a diversity of safe sites for seeds and seedlings (Urbanska, 1997;Peach and Zedler, 2006). Diverse microtopography can protect seedlings by providing areas with varying environmental conditions (i.e., differing temperatures, soil characteristics, redox levels, and water retention abilities) and has been shown to improve plant establishment, survival, and species richness in restorations (Urbanska, 1997;Peach and Zedler, 2006;Fivash et al, 2020;Mossman et al, 2020;Ott et al, 2020). Furthermore, the heterogeneity at a site can result in more complex plant communities and facilitate the development of ecosystem functions (Larkin et al, 2016).…”
Section: Microtopographymentioning
confidence: 99%
“…One strong candidate abiotic variable with which to manipulate seedling establishment may be found in the pioneer zone of salt marshes. Here, raised sediment surfaces are reported to have growth‐amplifying effects on young salt‐marsh recruits (Fivash et al 2020 , Mossman et al 2020 ). This may be due to special conditions within raised sediment platforms, from which water can easily drain over the low‐tide interval (Fagherazzi and Mariotti 2012 ).…”
Section: Introductionmentioning
confidence: 98%
“…These structures act as "barriers" or "shelters," which can effectively trap and retain (positively buoyant) seeds when they periodically contact with the substrate during the semi-diurnal tidal cycle (Wang et al 2018;Xie et al 2019;Qiu et al 2021). Interestingly, recent studies have reported that seedling establishment at new sites tends to occur on raised micro-topography covered by biostabilizers (such as diatom biofilms and fibrous algae Vaucheria; Fivash et al 2020;Van de Vijsel et al 2020), implying that biostabilizers may also provide a viable conduit for trapping and retaining the dispersed (germinated) seeds. Moreover, these biostabilizers can shape the local microhabitat by affecting sediment erodibility (Van de Vijsel et al 2020), water content, and dissolved oxygen content (Fivash et al 2020), and may therefore regulate the rooting rate of seeds, affecting their anchoring ability.…”
Section: Can We Explain Observed Rapid Colonization In the Field?mentioning
confidence: 99%